2021
DOI: 10.1055/s-0041-1723966
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Pediatric Soft Tissue Tumors and Tumor-like Conditions

Abstract: Lumps and bumps are frequently seen in children, and the vast majority are a result of trauma, infection, or inflammation. True soft tissue neoplastic lesions are rare; however, their wide and complex classifications make these lesions challenging to manage. Imaging features are usually nonspecific, and a reasonable list of differential diagnoses can be generated following consideration of the clinical presentation, age, and anatomical location of the lesion. In this article, we offer a practical approach to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(211 reference statements)
0
1
0
Order By: Relevance
“…However, due to calcification presented in few cases, our classification did not distinguish between coarse or minimal calcification, and we also considered intralesional phleboliths as calcification. Previous studies have suggested that certain malignant masses, such as neuroblastomas, are more likely to exhibit calcification 25 , 26 . Therefore, radiologists should carefully evaluate calcification as it may carry diagnostic significance.…”
Section: Discussionmentioning
confidence: 98%
“…However, due to calcification presented in few cases, our classification did not distinguish between coarse or minimal calcification, and we also considered intralesional phleboliths as calcification. Previous studies have suggested that certain malignant masses, such as neuroblastomas, are more likely to exhibit calcification 25 , 26 . Therefore, radiologists should carefully evaluate calcification as it may carry diagnostic significance.…”
Section: Discussionmentioning
confidence: 98%